Burden of Non-communicable Diseases among Patients Admitted in Medical Ward of a Hospital in Mountainous Region of Nepal - Anup Mangal Samal (Journal of Karnali Academy of Health Sciences, 2021)
Background: Non-communicable diseases (NCDs) are medical conditions or diseases that are non-transmissible from one person to another. NCDs have become the leading cause of morbidity and mortality worldwide. The objective of this study is to determine the burden of NCDs in a tertiary level general hospital in a mountainous region of Nepal.